Apakah Teknologi Media Baru Netral? - Munadhil Abdul Muqsith (UIN Syarif Hidayatullah Jakarta, 2022)
This paper is to explain Arnold Pacey about the neutrality of technology which was written in 1983 in the book The Culture of Technology. The author is interested in connecting the neutrality of new media technology that is revolutionizing human life in the 21st century. As if the world is borderless and has no boundaries, the exchange of information is so fast but there are also many negative impacts. The hegemony of technology companies such as Silicon Valley, Shenzhen, Stockholm, Tokyo, and Bengaluru is a concern for technology neutrality as well as data security and privacy. The author concludes that technology must be balanced with user media literacy. The government must also have special regulations to maintain the security and convenience of its people's data.